COVID-19 convalescent plasma composition and immunological effects in severe patients (2021)
ABSTRACT: Convalescent plasma (CP) has emerged as a treatment for COVID-19. However, the composition and mechanism of action are not fully known. Therefore, we undertook a two-phase controlled study in which, first the immunological and metabolomic status of recovered and severe patients were evaluated. Secondly, the 28-day effect of CP on the immune response in severe patients was assessed. Nineteen recovered COVID-19 patients, 18 hospitalized patients with severe disease, and 16 pre-pandemic controls were included. Patients with severe disease were treated with CP transfusion and standard therapy (i.e., plasma recipients, n = 9) or standard therapy alone (n = 9). Clinical and biological assessments were done on day 0 and during follow-up on days 4, 7, 14, and 28. Clinical parameters, viral load, total immunoglobulin (Ig) G and IgA anti-S1-SARS-CoV-2 antibodies, neutralizing antibodies (NAbs), autoantibodies, cytokines, T and B cells, and metabolomic and lipidomic profiles were examined. Total IgG and IgA anti-S1-SARS-CoV-2 antibodies were key factors for CP selection and correlated with NAbs. In severe COVID-19 patients, mostly interleukin (IL)-6 (P = <0.0001), IL-10 (P = <0.0001), IP-10 (P = <0.0001), fatty acyls and glycerophospholipids were higher than in recovered patients. Latent autoimmunity and anti–IFN–α antibodies were observed in both recovered and severe patients. COVID-19 CP induced an early but transient cytokine profile modification and increases IgG anti-S1-SARS-CoV-2 antibodies. At day 28 post-transfusion, a decrease in activated, effector and effector memory CD4+ (P < 0.05) and activated and effector CD8+ (P < 0.01) T cells and naïve B cells (P = 0.001), and an increase in non-classical memory B cells (P=<0.0001) and central memory CD4+ T cells (P = 0.0252) were observed. Moreover, IL-6/IFN-γ (P = 0.0089) and IL-6/IL-10 (P = 0.0180) ratios decreased in plasma recipients compared to those who received standard therapy alone. These results may have therapeutic implications and justify further post-COVID-19 studies.